CO2 Absorption in Polytetrafluoroethylene Membrane Microstructured Contactor Using Aqueous Solutions of Amines - Constantinou, Achilleas; Barrass, Simon; Gavriilidis, Asterios (My University, 2014)
Absorption of carbon dioxide (CO2) in aqueous solutions of monoethanolamine (MEA) and diethanolamine (DEA) was performed in a flat membrane microstructured contactor. The contactor had dimensions 192 mm × 97 mm (length × width). Liquid and gas flowed in channels of 0.2 mm and 0.85 mm depth, respectively, separated by a supported polytetrafluoroethylene (PTFE) membrane of 20 μm thickness containing 0.5-5 μm openings. The function of the membrane was to bring into direct contact the two phases (gas and liquid) without dispersing one phase into the other. Experiments were conducted with 1.6 M MEA and 1.6 M DEA solutions and 20 vol% CO2/N2 inlet concentration, with a fixed inlet molar ratio CO2/amine of 0.5 at room temperature. Substantial CO2 absorption was observed for gas residence time below 0.2 s. A mathematical model with no adjustable parameters was used to simulate the contactor, and experimental results were compared to model predictions in terms of CO2 removal efficiency. The model showed satisfactory agreement with experimental data. Both model and experimental results showed that MEA solution absorbed more CO2 than DEA. CO2 removal increased by increasing the contact area between gas and liquid, using an 8-channel PTFE membrane microstructured contactor.
Keywords: EthanolamineS; Mathematical models; Polytetrafluoroethylenes; Solutions